Endocrine Entropy - Sanjay Kalra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
This communication defines and describes the novel concept of endocrine entropy. The authors share insights regarding the various facets of entropy in endocrine epidemiology, physiology, clinical presentation and management. The discussion opens up a new way of approaching endocrinology. Recent advances in artificial intelligence, assessment and addressal of entropy may become integral part of endocrine diagnostics and therapeutics. Keywords: Artificial intelligence, basic science, endocrinology, hormones, physiology, technology